PENGARUH FAKTOR USIA, JENIS KELAMIN, DAN PENGETAHUAN TERHADAP SWAMEDIKASI OBAT - hilda suherman (Universitas Harapan Bangsa Purwokerto, 2018)
Abstract Self-medication is a human effort to treat diseases or symptoms of minor ailments such as fever, cough, flu, pain and others without a doctor's prescription. In practice, limited knowledge of drugs and their use can be a source of medication errors (medication error). This research was conducted with a cross sectional descriptive research method. Data was collected through a validated questionnaire filling technique. A total of 300 respondents involved in this study were selected by consecutive sampling method from 3 pharmacies in the city of Purwokerto which were determined proportionally according to the population of each pharmacy. Data were analyzed by Chi-square test and Fisher's test used Statistical Product and Servicer Solution (SPSS) version 17. The results showed that the patient's knowledge level was 22.6% classified as poor, 48% classified as moderate, and 29.4% classified as good. The use of self-medication is 26.3% irrational and 73.7% rational. Based on the results of the Chi-square and Fisher test, the level of knowledge is influenced by age, recent education, and occupation. While self-medication rationality is not influenced by gender, education and employment. Based on the results of the study, it was found that the patient's level of knowledge was classified as moderate with a percentage of 48%. While self-administered rationality is classified as rational with a percentage of 73.7%. Keywords: self-medication, pharmacy, rationality of drug use